Análise histológica do mesêntero de Chrysodeixis includens (Walker, 1858) (Lepidoptera: Noctuidae), exposta a Ricinus communis L. - Lima, Yuri Renan Alves de (2019)
Parallel to the world's agricultural development is the increase in the appearance of pest insects, especially the false-moth caterpillar, Chrysodeixis includens (Walker, 1858) (Lepidoptera: Noctuidae), which has soybeans as the main target, influencing in the profitability of its production. As a consequence, the scientific society has been searching for alternative methods to control this pest, highlighting the botanical extracts, since they have lower environmental impacts, and can act causing alterations mainly in the insect's midgut, damaging its physiology. In this way, the present work aims to analyze histologically the middle intestine (mesenteric) of C. includens exposed to hydroalcoholic extracts and purified fractions of Ricinus communis. Three caterpillars of C. includens were randomly collected in each treatment and controls, one at the end of 24h, 48h and 72h, which had been exposed to LC50 of purified fractions of R. communis. Thereafter, the caterpillars were killed and allocated in fixative solution for three hours, after which 70% alcohol was maintained. Then, they were dehydrated and underwent a historesin infiltration process, later being included in historesin and catalyst. The obtained blocks were cut in a microtome rotating manual EK MICRO 2.1 with a thickness of 3 to 4 μm. The sections were mounted on histological slides, stained with Hematoxylin - Eosin, and mounted with coverslips and balsam of Canada, analyzed and photographed under Axiophot - Zeiss optical photomicroscope for morphological study of the mesenteric. The present study showed that the middle intestine of C. includens did not present structural alterations for both the water and alcohol controls and for the purified fractions of R. communis, Hexane, Ethyl Acetate, Dichloromethane and Crude Extract evaluated in 24, 48 and 72 hours respectively, making further research necessary.